Genomic and biochemical analysis of repeatedly observed variants in DBT in individuals with maple syrup urine disease of Central American ancestry. Issue 9 (7th July 2022) - Billington, Charles J.; Chapman, Kimberly A.; Leon, Eyby; Meltzer, Beatrix W.; Berger, Seth I.; Olson, Matthew; Figler, Robert A.; Hoang, Steve A.; Wanxing, Cui; Wamhoff, Brian R.; Collado, M. Sol; Cusmano‐Ozog, Kristina
Abstract: Maple syrup urine disease (MSUD) is an intoxication‐type inherited metabolic disorder in which hyperleucinemia leads to brain swelling and death without treatment. MSUD is caused by branched‐chain alpha‐ketoacid dehydrogenase deficiency due to biallelic loss of the protein products from the genes BCKDHA, BCKDHB, or DBT, while a distinct but related condition is caused by loss of DLD . In this case series, eleven individuals with MSUD caused by two pathogenic variants in DBT are presented. All eleven individuals have a deletion of exon 2 (delEx2, NM_001918.3:c.48_171del); six individuals are homozygous and five individuals are compound heterozygous with a novel missense variant (NM_001918.5:c.916 T > C [p.Ser306Pro]) confirmed to be in trans. Western Blot indicates decreased amount of protein product in delEx2;c.916 T > C liver cells and absence of protein product in delEx2 homozygous hepatocytes. Ultrahigh performance liquid chromatography–tandem mass spectrometry demonstrates an accumulation of branched‐chain amino acids and alpha‐ketoacids in explanted hepatocytes. Individuals with these variants have a neonatal‐onset, non‐thiamine‐responsive, classical form of MSUD. Strikingly, the entire cohort is derived from families who immigrated to the Washington, DC, metro area from Honduras or El Salvador suggesting the possibility of a founder effect.